Photodisintegration of 9Be and the importance of the unbound 1/2+ state - Odsuren Myagmarjav; Kikuchi Yuma; Myo Takayuki; Aikawa Masayuki; Katō Kiyoshi (EPJ Web of Conferences, 2016)
The photodisintegration cross section of the 9Be(1/2+) state is investigated in a framework of the α + α + n three-body model. The 1/2+ state of 9Be locates just above the three-body threshold, and the s-wave neutron property of this state is a long-standing problem. It has been a topic of quite interest in relation to the breakup mechanism of 9Be into the 8Be(0+) + n and (α + α + n) channels.